Analyzing non-sentinel axillary metastases in patients with T3-T4 cN0 early breast cancer and tumor-involved sentinel lymph nodes undergoing breast-conserving therapy or mastectomy - Riedel, Fabian; Heil, Jörg; Feißt, Manuel; Moderow, Mareike; Au, Alexandra von; Domschke, Christoph; Michel, Laura L.; Schäfgen, Benedikt; Golatta, Michael; Hennigs, André (Breast cancer research and treatment, 2020)
In the ACOSOG Z0011 trial, completing axillary lymph node dissection (cALND) did not benefit patients with T1-T2 cN0 early breast cancer and 1-2 positive sentinel lymph nodes (SLN) undergoing breast-conserving surgery (BCT). This paper reports cALND rates in the clinical routine for patients who had higher (T3-T4) tumor stages and/or underwent mastectomy but otherwise met the ACOSOG Z0011 eligibility criteria. Aim of this study is to determine cALND time trends and non-sentinel axillary metastases (NSAM) rates to estimate occult axillary tumor burden.